A method for photocuring additive manufacturing of ceramic parts

By using a mixed paste of graded ceramic particles and organic solvents in photocured ceramic additive manufacturing, combined with freeze-drying and controlling heating conditions, the crack problem caused by gas discharge during degreasing in ceramic additive manufacturing is solved, and the manufacturing is shortened Cycles and improves the flexural strength of the product.

CN118026655BActive Publication Date: 2024-12-20JIANGNAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410125577.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2024-12-20
Estimated Expiration
2044-01-30

AI Technical Summary

Technical Problem

Existing photocured ceramic additive manufacturing materials are prone to cracks during degreasing, resulting in too long manufacturing cycles. Especially when ceramic components with a thickness of more than 10 mm are degreased, gas discharge paths are long, and failure to discharge gas in time will lead to cracks. , the existing solution is to reduce the thermal degreasing rate, resulting in the extended ceramic additive manufacturing cycle.

Method used

Using mixed photosensitive resin with organic solvents and ceramic particles that do not participate in the photo-solidation reaction, the photo-cured additive manufacturing paste is formed through homogenization and rolling processing, and the photo-curing and freeze-drying is carried out to generate fine holes, and the heating device is controlled. The atmosphere and temperature gradient are used to slow down the oxidation reaction, prevent the gas from being discharged too quickly during sintering, and sintering is performed using an inert gas and an oxygen mixture.

Benefits of technology

Through the use of graded ceramic particles and organic solvents, the thermal degreasing and sintering time of ceramic additive manufacturing is shortened, the manufacturing cycle is reduced, the flexural strength of the product is improved, and the production cycle of parts with thicker thickness is shortened from 10 days to 55 days. ~80 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118026655B_ABST
    Figure CN118026655B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for photocuring additive manufacturing of ceramic parts, the steps are as follows: the first step: preparing a resin premix, the mass of the organic solvent not participating in the photocuring reaction is 20% to 40% of the mass of the resin premix, and the photosensitive resin is a mixture of a monofunctional resin, a bifunctional resin and a trifunctional resin; the second step: obtaining a photocuring additive manufacturing paste; the third step: performing photocuring forming to obtain a green body; the fourth step: cleaning the green body, and then freeze-drying until fine holes appear on the surface of the green body; the fifth step: thermal degreasing; the sixth step: sintering. The purpose of the present invention is to provide a manufacturing method for thicker parts based on photocuring ceramic additive manufacturing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photocuring ceramic additive manufacturing, and in particular to a method for manufacturing ceramic parts using photocuring additive manufacturing. Background Art

[0002] Additive manufacturing is a rapid prototyping technology that uses a digital model file as the basis, uses powdered adhesive materials, and prints objects layer by layer. As additive manufacturing technology can construct complex structures in a relatively short period of time, it has gradually been widely studied and applied in mold manufacturing, industrial design, medical industry and other fields.

[0003] The bondable materials used in additive manufacturing can be either metal materials or non-metallic materials, depending on the industry in which they are used. In the medical industry, for the convenience of patients' daily lives, non-metallic materials, such as ceramic materials, are first considered as bondable materials for additive manufacturing.

[0004] The existing photocuring ceramic additive manufacturing materials have the following problems: in the process of using ceramic materials to prepare additive manufacturing objects, degreasing of ceramics is an essential process flow. In medical devices, additive manufacturing of objects with a thickness of more than 10 mm is often required. Thicker ceramic components require a longer gas exhaust path during the degreasing process, and often large cracks are generated during degreasing due to failure to exhaust gas in time. In order to prevent the occurrence of cracks, the solution of the existing process is to reduce the thermal degreasing rate as much as possible. Currently, thermal degreasing of objects with a thickness of more than 10 mm usually takes 10 days or even longer, but this also makes the ceramic additive manufacturing cycle too long. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a method for manufacturing thicker parts based on photocuring additive manufacturing of ceramic materials.

[0006] Technical solution: The method for photocuring additive manufacturing of ceramic parts described in the present invention comprises the following steps:

[0007] The first step: mixing an organic solvent that does not participate in the photocuring reaction with a photosensitive resin to obtain a resin premix, wherein the mass of the organic solvent that does not participate in the photocuring reaction is 20% to 40% (mass ratio) of the mass of the resin premix, and the photosensitive resin is a mixture of a monofunctional resin, a difunctional resin and a trifunctional resin. The speed at which a pure monofunctional resin participates in the crosslinking reaction during the photocuring process is relatively slow, and a pure trifunctional resin undergoes a fast crosslinking reaction and releases a large amount of heat;

[0008] Step 2: Add a photoinitiator to the mixture obtained in the first step, the mass of the photoinitiator is 1.5-2.5% of the mass of the photosensitive resin premix, and then add graded ceramic particles and dispersants three times, the amount of the graded ceramic particles added three times is 50%, 40% and 10% of the total mass of the graded ceramic particles respectively, the mass of the dispersant is 1-3% of the mass of the graded ceramic particles, after each addition of the graded ceramic particles and the dispersant, put the mixture into a homogenizer for homogenization, after the graded ceramic particles and the dispersant are added, put it into a roller press for multiple rolling to obtain a light-cured additive manufacturing paste, and put the light-cured additive manufacturing paste into a vacuum machine for degassing;

[0009] Step 3: Place the photocurable additive manufacturing paste obtained in the second step into an additive manufacturing device for photocuring to obtain a green body;

[0010] Step 4: washing the green body obtained in the step 3, and then freeze-drying the washed green body until fine holes appear on the surface of the green body;

[0011] Step 5: placing the freeze-dried green body into a heating device for thermal degreasing, introducing an inert gas into the heating device at a rate of 0.5 L / min, raising the temperature in the heating device from room temperature to 200°C at a heating rate of 0.9-1.2°C / min; raising the temperature from 200°C to 300°C at a heating rate of 0.4-0.6°C / min; raising the temperature from 300°C to 400°C at a heating rate of 0.08-0.12°C / min, and keeping the temperature at 300°C, 325°C, 350°C and 400°C for 2 hours respectively; raising the temperature from 400°C to 600°C at a heating rate of 0.2-0.4°C / min; keeping the temperature at 600°C for 0.8-1.2 hours;

[0012] Step 6: Sintering, the temperature in the heating device is increased from 600°C to 800°C, and the heating rate is 0.9-1.2°C / min; at 800°C, a mixed gas of oxygen and inert gas is introduced into the heating device, and the content of oxygen accounts for 5-8% (volume ratio) of the mixed gas. The introduction rate of the mixed gas is 0.1L / min, and the temperature in the heating device is increased from 800°C to 1000°C, and the heating rate is 1.3-1.7°C / min; at 1000°C, a second mixed gas of oxygen and inert gas is introduced into the heating device, and the content of oxygen accounts for 5% to 8% (volume ratio) of the second mixed gas. The temperature is raised from 1000℃ to 1350℃ at a rate of 0.9-1.2℃ / min. At 1350℃, air is introduced into the heating device at a rate of 1L / min. The temperature is raised from 1350℃ to the maximum sintering temperature at a rate of 0.9-1.2℃ / min. The temperature is kept at the maximum sintering temperature for 0.5-4 hours. The temperature is lowered from the maximum sintering temperature to 1000℃ at a rate of 0.9-1.2℃ / min. Finally, the green body is naturally cooled in the heating device from 1000℃. A large amount of carbon will remain after degreasing. Controlling the oxygen content in the atmosphere can slow down the oxidation reaction and prevent cracks from being generated due to a large amount of gas in a short time during sintering.

[0013] Furthermore, in the first step, the mass ratio of the monofunctional resin, the difunctional resin and the trifunctional resin is 1:1.5:2.5 to 1:2.5:4.

[0014] Furthermore, the monofunctional photosensitive resin is one or a mixture of any two of hydroxyethyl methacrylate, lauryl acrylate, isobornyl acrylate, phenoxyethyl acrylate or lauric acid methacrylate; the bifunctional photosensitive resin is one or a mixture of any two of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate or dipropylene glycol diacrylate; and the trifunctional photosensitive resin monomer is propoxylated glycerol triacrylate or ethoxylated trimethylolpropane triacrylate.

[0015] Furthermore, the organic solvent not participating in the photocuring reaction in the first step is one of N,N-dimethylformamide, isopropanol, and N-methylpyrrolidone, or any mixture thereof.

[0016] Furthermore, in the fourth step, a flowing cleaning liquid is used to clean the green body, wherein the cleaning liquid is obtained by mixing a resin monomer, isopropyl alcohol and polyethylene glycol in a mass ratio of 1:1:1, and the resin monomer is one of hydroxyethyl methacrylate, lauryl acrylate, isobornyl acrylate, phenoxyethyl acrylate or lauric acid methacrylate.

[0017] Furthermore, the organic solvent not participating in the photocuring reaction in the first step also includes polyethylene glycol.

[0018] Furthermore, when the organic solvent not participating in the photocuring reaction in the first step includes polyethylene glycol, a flowing alkaline solution is used to clean the green body in the fourth step.

[0019] Furthermore, the polyethylene glycol described in the first and fourth steps can only be one of short-chain PEG200, PEG400, and PEG600 or any mixture thereof. Short-chain polyethylene glycol is more likely to seep into the green body with the alkaline solution, and fine pores are generated on the surface of the green body during the seepage process.

[0020] Furthermore, the alkaline solution is an ammonium nitrate solution, the pH value of the ammonium nitrate solution is pH 8.5-9.5, and the ammonium nitrate can be decomposed at high temperature and will not remain in the final product.

[0021] Furthermore, in the second step, the solid content G of the photocurable additive manufacturing paste is ≥ 60 vol% (mass ratio). The solid content refers to the volume proportion of ceramics in the photocurable additive manufacturing paste.

[0022] Furthermore, the parameters of the additive manufacturing equipment in the third step are a light intensity of 50 to 150 mW, a laser printing speed of 1000 to 14000 mm / s, a printing spacing of 0.02 to 0.04 mm, and a printing layer thickness of 40 to 80 μm.

[0023] Furthermore, the graded ceramic particles in the second step are a mixture of ceramic particles with a particle size of 200 nanometers and ceramic particles with a particle size of 5 to 25 micrometers, and the mass ratio of the ceramic particles with a particle size of 200 nanometers to the ceramic particles with a particle size of 5 to 25 micrometers is 3:1 to 2:1.

[0024] Furthermore, the ceramic particles with a particle size of 5 to 25 microns are obtained by spray granulation of ceramic powder with an original particle size of 20 to 50 nanometers.

[0025] Furthermore, the material of the ceramic particles may be any ceramic, such as any one of aluminum oxide, zirconium oxide, magnesium oxide, yttrium oxide, magnesium aluminum spinel or hydroxyapatite, or other ceramics.

[0026] Furthermore, the maximum sintering temperature is related to the ceramic material. When the material of the ceramic particles is aluminum oxide, the maximum sintering temperature is 1700°C; when the ceramic material is zirconium oxide, the maximum sintering temperature is 1500°C; when the ceramic material is magnesium oxide or yttrium oxide, the maximum sintering temperature is 1800°C.

[0027] Furthermore, the heating device in the fifth step is an atmosphere furnace.

[0028] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. The graded ceramic particles are a mixture of ceramic particles with a particle size of 200 nanometers and ceramic particles with a particle size of 5 to 25 micrometers, and the ceramic particles of 5 to 25 micrometers are obtained by spray granulation of ceramic powder with an original particle size of 20 nanometers to 50 nanometers. The ceramic powder with an original particle size of 20 nanometers to 50 nanometers has high activity, and the ceramic particles of 5 to 25 micrometers obtained after spray granulation have a small specific surface area, which is easier to disperse in subsequent processes. Therefore, the graded ceramic particles have the advantages of high activity and good dispersibility; 2. An organic solvent that does not participate in the photocuring reaction is added to the high-solid content paste. The organic solvent that does not participate in the photocuring reaction dilutes the resin premix, reduces the content of the photosensitive resin per unit volume, and makes the photosensitive resin more evenly distributed in the paste, laying a good foundation for subsequent better degreasing; 3. , N-dimethylformamide, isopropanol, and N-methylpyrrolidone are three organic solvents with low boiling points, and can be freeze-dried to seep into the green body faster, and fine holes are generated on the surface of the green body during the seepage process. If the organic solvent that does not participate in the photocuring reaction also includes polyethylene glycol, when the green body is cleaned with a flowing alkaline solution, the polyethylene glycol will also follow the alkaline solution to seep into the green body, and fine holes will be generated on the surface of the green body during the seepage process. The fine holes generated are conducive to the discharge of gas during subsequent thermal degreasing, and prevent the gas from being discharged too quickly during the degreasing process and causing cracks. Therefore, the time of thermal degreasing and sintering can be shortened as much as possible, the manufacturing cycle can be reduced, and the flexural strength of the product can be increased; 4. After using the present invention, the production cycle of thicker parts manufactured based on photocuring ceramic additive manufacturing materials is shortened from 10 days (i.e., 240 hours) to 55-80 hours, and the production cycle is greatly shortened. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a flow chart of the present invention.

[0030] Figure 2 It is a time trend diagram of thermal debinding and sintering of the present invention.

[0031] Figure 3 A close-up of a thicker component produced using existing manufacturing processes.

[0032] Figure 4 A partial enlarged view of a thicker component made according to the present invention.

[0033] Figure 5 This is an enlarged view of the surface of the green body after freeze-drying. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0035] Example 1

[0036] The existing method steps for manufacturing thicker parts are as follows:

[0037] Step 1: Prepare a photosensitive resin monomer mixture (without other chemical solvents);

[0038] Step 2: Add photoinitiator to the mixture obtained in the first step, the mass of the photoinitiator is 1.5-2.5% of the mass of the photosensitive resin premix, and then add graded alumina particles and dispersant three times, the amount of graded alumina particles added three times is 50%, 40% and 10% of the total mass of the graded alumina particles respectively, the mass of the dispersant is 1-3% of the mass of the graded alumina particles, after each addition of graded alumina particles and dispersant, put the mixture into a homogenizer for homogenization, after the graded alumina particles and dispersant are added, put it into a roller press for multiple rolling, A photocurable additive manufacturing paste is obtained, and the photocurable additive manufacturing paste is placed in a vacuum machine for degassing treatment, wherein the solid content G of the photocurable additive manufacturing paste is ≥60 vol%, the graded alumina particles are a mixture of alumina particles with a particle size of 200 nanometers and alumina particles with a particle size of 5 to 25 micrometers, the mass ratio of the alumina particles with a particle size of 200 nanometers to the alumina particles with a particle size of 5 to 25 micrometers is 3:1 to 2:1, and the alumina particles with a particle size of 5 to 25 micrometers are obtained by spray granulation of alumina powder with an original particle size of 20 nanometers to 50 nanometers;

[0039] Step 3: Place the photocurable additive manufacturing paste obtained in the second step into an additive manufacturing device for photocuring to obtain a green body;

[0040] Step 4: Clean the green body obtained after the third step with flowing isopropyl alcohol and then dry it;

[0041] Step 5: Place the dried green body into an atmosphere furnace for thermal degreasing, introduce argon into the atmosphere furnace at a rate of 0.5 L / min, and raise the temperature in the atmosphere furnace from room temperature to 200°C at a heating rate of 0.3°C / min; from 200°C to 300°C at a heating rate of 0.1°C / min; from 300°C to 400°C at a heating rate of 0.03°C / min, and keep warm at 300°C, 325°C, 350°C and 400°C for 2 hours respectively; from 400°C to 600°C at a heating rate of 0.05°C / min; keep warm at 600°C for 1 hour;

[0042] Step 6: Sintering. The atmosphere in the atmosphere furnace is air. The temperature in the atmosphere furnace rises from 600℃ to 800℃, and the heating rate is 0.3℃ / min; the temperature in the atmosphere furnace rises from 800℃ to 1000℃, and the heating rate is 0.4℃ / min; the temperature rises from 1000℃ to 1350℃, and the heating rate is 0.3℃ / min; the temperature rises from 1350℃ to 1700℃, and the heating rate is 0.25℃ / min; keep warm at 1700℃ for 2.5 hours; the temperature drops from 1700℃ to 1000℃, and the cooling rate is 0.28℃ / min; finally, cool naturally from 1000℃ in the atmosphere furnace.

[0043] The existing method for manufacturing thicker parts takes 241 hours, and the enlarged partial view of the thicker parts is as follows: Figure 3 As shown, there are relatively large cracks and the flexural strength is only 180 MPa.

[0044] Example 2

[0045] See attached Figure 1 to Figure 5 The present invention provides a method for photocuring additive manufacturing of ceramic parts, comprising the following steps:

[0046] The first step: mixing isopropyl alcohol with a photosensitive resin to obtain a photosensitive resin premix, wherein the mass of the isopropyl alcohol is 25% of the mass of the resin premix, and the photosensitive resin is a mixture of hydroxyethyl methacrylate, 1,6-hexanediol diacrylate and propoxylated glycerol triacrylate in a mass ratio of 1:2:3;

[0047] Step 2: Add photoinitiator to the mixture obtained in the first step, the mass of the photoinitiator is 1.5-2.5% of the mass of the photosensitive resin premix, and then add graded alumina particles and dispersant three times, the amount of graded alumina particles added three times is 50%, 40% and 10% of the total mass of the graded alumina particles respectively, the mass of the dispersant is 1-3% of the mass of the graded alumina particles, after each addition of graded alumina particles and dispersant, put the mixture into a homogenizer for homogenization, after the graded alumina particles and dispersant are added, put it into a roller press for multiple rolling, A photocurable additive manufacturing paste is obtained, and the photocurable additive manufacturing paste is placed in a vacuum machine for degassing treatment, wherein the solid content G of the photocurable additive manufacturing paste is ≥60 vol%, the graded alumina particles are a mixture of alumina particles with a particle size of 200 nanometers and alumina particles with a particle size of 5 to 25 micrometers, the mass ratio of the alumina particles with a particle size of 200 nanometers to the alumina particles with a particle size of 5 to 25 micrometers is 3:1 to 2:1, and the alumina particles with a particle size of 5 to 25 micrometers are obtained by spray granulation of alumina powder with an original particle size of 20 nanometers to 50 nanometers;

[0048] Step 3: Place the photocurable additive manufacturing paste obtained after the second step into the additive manufacturing equipment for photocuring forming to obtain a green body. The parameters of the additive manufacturing equipment are: light intensity of 70mW, laser printing speed of 8000mm / s, printing spacing of 0.03mm, and printing layer thickness of 50μm;

[0049] Step 4: washing the green body obtained in the third step with flowing deionized water, and then freeze-drying the washed green body until fine holes appear on the surface of the green body;

[0050] Step 5: Place the freeze-dried green body into an atmosphere furnace for thermal degreasing, introduce argon into the atmosphere furnace at a rate of 0.5 L / min, and raise the temperature in the atmosphere furnace from room temperature to 200°C at a heating rate of 1°C / min; the temperature rises from 200°C to 300°C at a heating rate of 0.5°C / min; the temperature rises from 300°C to 400°C at a heating rate of 0.1°C / min, and is kept at 300°C, 325°C, 350°C and 400°C for 2 hours respectively; the temperature rises from 400°C to 600°C at a heating rate of 0.3°C / min; and is kept at 600°C for 1 hour;

[0051] Step 6: Sintering, the temperature in the atmosphere furnace rises from 600℃ to 800℃, and the heating rate is 1℃ / min; at 800℃, the first mixed gas of oxygen and argon is introduced into the atmosphere furnace, and the oxygen content accounts for 6% (volume ratio) of the first mixed gas. The introduction rate of the mixed gas is 0.1L / min, and the temperature in the atmosphere furnace rises from 800℃ to 1000℃, and the heating rate is 1.5℃ / min; at 1000℃, the second mixed gas of oxygen and inert gas is introduced into the atmosphere furnace, and the oxygen content accounts for 6% (volume ratio) of the first mixed gas. The content accounts for 12% (volume ratio) of the second mixed gas, the temperature is increased from 1000℃ to 1350℃, and the heating rate is 1℃ / min; at 1350℃, air is introduced into the atmosphere furnace, and the air introduction rate is 1L / min, the temperature is increased from 1350℃ to 1700℃, and the heating rate is 1℃ / min; keep warm at 1700℃ for 2.5 hours; the temperature is reduced from 1700℃ to 1000℃, and the cooling rate is 1℃ / min; finally, it is naturally cooled from 1000℃ in the atmosphere furnace.

[0052] The enlarged partial image of the thicker part is shown in Figure 4 As shown, there are no cracks and the flexural strength can reach 480MPa.

[0053] Example 3

[0054] See attached Figure 1 to Figure 5 The present invention provides a method for photocuring additive manufacturing of ceramic parts, comprising the following steps:

[0055] The first step: N, N-dimethylformamide, polyethylene glycol and photosensitive resin are mixed to obtain a photosensitive resin premix, wherein the mass of the mixed N, N-dimethylformamide and polyethylene glycol is 35% of the mass of the resin premix, and the photosensitive resin is prepared by mixing isobornyl acrylate, dipropylene glycol diacrylate and ethoxylated trimethylolpropane triacrylate in a mass ratio of 1:2.5:3.5;

[0056] Step 2: Add a photoinitiator to the mixture obtained in the first step, the mass of the photoinitiator is 2.2% of the mass of the photosensitive resin premix, and then add graded alumina particles and dispersants three times, the amount of graded alumina particles added three times is 50%, 40% and 10% of the total mass of the graded alumina particles respectively, the mass of the dispersant is 2.5% of the mass of the graded alumina particles, after each addition of the graded alumina particles and the dispersant, put the mixture into a homogenizer for homogenization, after the graded alumina particles and the dispersant are added, put it into a roller press for multiple rolling to obtain A photocurable additive manufacturing paste, wherein the photocurable additive manufacturing paste is placed in a vacuum machine for degassing treatment, wherein the solid content G of the photocurable additive manufacturing paste is ≥ 60 vol%, the graded alumina particles are a mixture of alumina particles with a particle size of 200 nanometers and alumina particles with a particle size of 5 to 25 micrometers, the mass ratio of the alumina particles with a particle size of 200 nanometers to the alumina particles with a particle size of 5 to 25 micrometers is 3:1 to 2:1, and the alumina particles with a particle size of 5 to 25 micrometers are obtained by spray granulation of alumina powder with an original particle size of 20 nanometers to 50 nanometers;

[0057] Step 3: Place the photocurable additive manufacturing paste obtained after the second step into the additive manufacturing equipment for photocuring forming to obtain a green body. The parameters of the additive manufacturing equipment are light intensity of 115mW, laser printing speed of 5000mm / s, printing spacing of 0.018mm, and printing layer thickness of 45μm.

[0058] Step 4: washing the green body obtained after the step 3 with a flowing ammonium nitrate solution, wherein the pH value of the ammonium nitrate solution is 8.5 to 9.5, and then freeze-drying the washed green body until fine holes appear on the surface of the green body;

[0059] Step 5: Place the freeze-dried green body into an atmosphere furnace for thermal degreasing, introduce inert gas into the atmosphere furnace, the introduction rate of inert gas is 0.5L / min, the temperature in the atmosphere furnace is increased from room temperature to 200°C, the heating rate is 1.1°C / min; the temperature is increased from 200°C to 300°C, the heating rate is 0.55°C / min; the temperature is increased from 300°C to 400°C, the heating rate is 0.11°C / min, during which the four temperature points of 300°C, 325°C, 350°C and 400°C are kept warm for 2 hours respectively; the temperature is increased from 400°C to 600°C, the heating rate is 0.37°C / min; keep warm at 600°C for 0.9 hours;

[0060] Step 6: Sintering, the temperature in the atmosphere furnace rises from 600℃ to 800℃, and the heating rate is 1.15℃ / min; at 800℃, a first mixed gas of oxygen and inert gas is introduced into the atmosphere furnace, and the oxygen content accounts for 7% (volume ratio) of the first mixed gas. The introduction rate of the mixed gas is 0.1L / min, and the temperature in the atmosphere furnace rises from 800℃ to 1000℃, and the heating rate is 1.6℃ / min; at 1000℃, a second mixed gas of oxygen and inert gas is introduced into the atmosphere furnace, and the oxygen content accounts for The second mixed gas was 13% (volume ratio), the temperature was increased from 1000°C to 1350°C, and the heating rate was 1.12°C / min; at 1350°C, air was introduced into the atmosphere furnace, and the air introduction rate was 1L / min, the temperature was increased from 1350°C to 1700°C, and the heating rate was 1.12°C / min; it was kept at 1700°C for 0.5 to 4 hours; the temperature was reduced from 1700°C to 1000°C, and the cooling rate was 1.11°C / min; finally, it was naturally cooled from 1000°C in the atmosphere furnace.

[0061] The enlarged partial image of the thicker part is shown in Figure 4 As shown, there are no cracks and the flexural strength can reach 560MPa.

[0062] The surface of the green body obtained after the third step is as follows after washing and freeze drying: Figure 5 As shown in the figure, the black dots are tiny holes on the surface of the green body.

Claims

1. A method for photocuring additive manufacturing of ceramic parts, comprising the following steps: The first step: mixing an organic solvent that does not participate in the photocuring reaction with a photosensitive resin to obtain a resin premix, wherein the mass of the organic solvent that does not participate in the photocuring reaction is 20wt% to 40wt% of the mass of the resin premix, and the photosensitive resin is a mixture of a monofunctional resin, a difunctional resin, and a trifunctional resin. The organic solvent that does not participate in the photocuring reaction includes polyethylene glycol, and the organic solvent that does not participate in the photocuring reaction also includes one of N, N-dimethylformamide, isopropanol, and N-methylpyrrolidone, or any mixture thereof; Step 2: Add a photoinitiator to the resin premix obtained in the first step, the mass of the photoinitiator is 1.5-2.5% of the mass of the resin premix, and then add graded ceramic particles and dispersants three times, the amount of the graded ceramic particles added three times is 50%, 40% and 10% of the total mass of the graded ceramic particles respectively, the mass of the dispersant is 1-3% of the mass of the graded ceramic particles, and after each addition of the graded ceramic particles and the dispersant, the mixture is homogenized in a homogenizer. After the graded ceramic particles and the dispersant are added, Put it into a roller press and roll it several times to obtain a photocurable additive manufacturing paste, and put the photocurable additive manufacturing paste into a vacuum machine for degassing treatment, wherein the graded ceramic particles are a mixture of ceramic particles with a particle size of 200 nanometers and ceramic particles with a particle size of 5 to 25 micrometers, and the mass ratio of the ceramic particles with a particle size of 200 nanometers to the ceramic particles with a particle size of 5 to 25 micrometers is 3:1 to 2:1, and the ceramic particles with a particle size of 5 to 25 micrometers are obtained by spray granulation of ceramic powder with an original particle size of 20 nanometers to 50 nanometers; Step 3: Place the photocurable additive manufacturing paste obtained in the second step into an additive manufacturing device for photocuring to obtain a green body; Step 4: washing the green body obtained in the third step with a flowing ammonium nitrate solution, and then freeze-drying the washed green body until fine holes appear on the surface of the green body, wherein the pH value of the ammonium nitrate solution is pH 8.5-9.5; Step 5: placing the freeze-dried green body into a heating device for thermal degreasing, introducing an inert gas into the heating device at a rate of 0.5 L / min, raising the temperature in the heating device from room temperature to 200°C at a heating rate of 0.9-1.2°C / min; raising the temperature from 200°C to 300°C at a heating rate of 0.4-0.6°C / min; raising the temperature from 300°C to 400°C at a heating rate of 0.08-0.12°C / min, and keeping the temperature at 300°C, 325°C, 350°C and 400°C for 2 hours respectively; raising the temperature from 400°C to 600°C at a heating rate of 0.2-0.4°C / min; keeping the temperature at 600°C for 0.8-1.2 hours; Step 6: Sintering, the temperature in the heating device is increased from 600°C to 800°C, and the heating rate is 0.9-1.2°C / min; at 800°C, a first mixed gas of oxygen and inert gas is introduced into the heating device, and the content of oxygen accounts for 5-8% of the first mixed gas, and the introduction rate of the mixed gas is 0.1L / min. The temperature in the heating device is increased from 800°C to 1000°C, and the heating rate is 1.3-1.7°C / min; at 1000°C, a second mixed gas of oxygen and inert gas is introduced into the heating device, and the content of oxygen accounts for 5-8% of the first mixed gas. The invention discloses a method for preparing a sintered product comprising: adding 10 to 15% of the two mixed gases, and the temperature is increased from 1000°C to 1350°C at a heating rate of 0.9 to 1.2°C / min; at 1350°C, air is introduced into the heating device at a rate of 1 L / min, and the temperature is increased from 1350°C to the maximum sintering temperature at a heating rate of 0.9 to 1.2°C / min; the sintering temperature is kept at the maximum sintering temperature for 0.5 to 4 hours; the temperature is reduced from the maximum sintering temperature to 1000°C at a cooling rate of 0.9 to 1.2°C / min; and finally, the sintered product is naturally cooled from 1000°C in the heating device.

2. The method for photocuring additive manufacturing of ceramic parts according to claim 1, characterized in that: The mass ratio of the monofunctional resin, the difunctional resin and the trifunctional resin in the first step is 1:1.5:2.5 to 1:2.5:

4.

3. A method for photocuring additive manufacturing of ceramic parts according to claim 1 or 2, characterized in that: The monofunctional photosensitive resin is one of hydroxyethyl methacrylate, lauryl acrylate, isobornyl acrylate, phenoxyethyl acrylate or lauric acid methacrylate or a mixture of any multiple thereof; the bifunctional photosensitive resin is one of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate or dipropylene glycol diacrylate or a mixture of any multiple thereof; the trifunctional photosensitive resin monomer is propoxylated glycerol triacrylate or ethoxylated trimethylolpropane triacrylate.

4. The method for photocuring additive manufacturing of ceramic parts according to claim 1, characterized in that: In the second step, the solid content G of the photocuring additive manufacturing paste is ≥ 60 vol%.

5. The method for photocuring additive manufacturing of ceramic parts according to claim 1, characterized in that: The parameters of the additive manufacturing equipment described in the third step are a light intensity of 50 to 150 mW, a laser printing speed of 1000 to 14000 mm / s, a printing spacing of 0.02 to 0.04 mm, and a printing layer thickness of 40 to 80 μm.

Citation Information

Patent Citations

  • 3D ceramic body printing method

    CN107584631A

  • Novel ceramic slurry as well as ceramic prepared by same and application thereof

    CN108658607A

  • Photocurable composition

    CN110436944A

  • Photosensitive resin-based carbon source / silicon carbide ceramic slurry, method for preparing porous carbon / silicon carbide green body, structural member and preparation method of structural member

    CN111116205A

  • Photocuring ceramic slurry for 3D printing and pretreatment method of formed green body

    CN113603467A